Development of a Busy Book as a Learning Medium to Enhance Numeracy Skills in Early Childhood - Hamid Patilima; Lina Marlina (Kirana Publisher (KNPub), 2026)
This study aimed to determine the level of validity and attractiveness of the developed Busy Book learning media in improving early childhood numeracy skills, as well as to examine students’ responses to the use of Busy Book media in enhancing counting abilities at KB Nurul Fajriah Al-Hasanah. The study employed a Research and Development (R&D) method using the ADDIE development model. Data analysis techniques were based on descriptive data obtained from expert validation, involving subject-matter experts, media experts, and educational practitioners. The validity assessment of the Busy Book media conducted by material experts, media experts, and practitioners yielded an average score of 93%, categorized as very valid. Learners’ interest in using the Busy Book media reached 95%, indicating a very high level of attractiveness. Furthermore, children’s numeracy skills after using the Busy Book achieved the category of Very Well Developed. Based on teacher assessments, all 12 participating students (100%) strongly agreed that children’s counting abilities improved after using the Busy Book media. The findings conclude that the Busy Book is feasible and effective for use in early childhood numeracy learning.